2018
DOI: 10.5194/isprs-archives-xlii-5-305-2018
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Impacts of Climate Change on Teak and Sal Landscape Using Modis Time Series Data

Abstract: <p><strong>Abstract.</strong> Climate change poses a severe threat to the forest ecosystems by impacting its productivity, species composition and forest biodiversity at global and regional level. The scientific community all over the world is using remote sensing techniques to monitor and assess the impact of climate change on forest ecosystems. The consistent time series data provided by MODIS is immensely used for developing a different type of Vegetation indices like NDVI (Normalized diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The response of NDVI to climate factors may differ according to vegetation type and growth phase [157] with obvious time-lag effects [13,22,104]. In some regions, NDVI variation is due to variation in precipitation [25,66,102,[158][159][160]; in other regions, temperature is a major influencing factor in the variation of NDVI [34,46,92,93]. However, for the main cases of NDVI changes are dependent on both temperature and precipitation climatic factors [30,93,161,162].…”
Section: Correlation and Time-lag Effects Between Landsat Ndvi Data S...mentioning
confidence: 99%
See 1 more Smart Citation
“…The response of NDVI to climate factors may differ according to vegetation type and growth phase [157] with obvious time-lag effects [13,22,104]. In some regions, NDVI variation is due to variation in precipitation [25,66,102,[158][159][160]; in other regions, temperature is a major influencing factor in the variation of NDVI [34,46,92,93]. However, for the main cases of NDVI changes are dependent on both temperature and precipitation climatic factors [30,93,161,162].…”
Section: Correlation and Time-lag Effects Between Landsat Ndvi Data S...mentioning
confidence: 99%
“…Many previous studies have reported strong correlations between NDVI and main climatic factors of precipitation and temperature [89][90][91][92][93]. Furthermore, the relationships between climatic factors and NDVI/vegetation are different in various geographical regions and types of land cover [41,88,94].…”
Section: Introductionmentioning
confidence: 99%
“…The response of NDVI to climate factors may differ according to vegetation type and growth phase [164] with obvious lag-time effect [15], [26], [104]. In some regions, NDVI variation is due to variation in precipitation [29], [102], [165]- [167] in other regions, temperature is a major influencing factor in the variation of NDVI [34], [46], [92], [93]. However, for the main cases of NDVI changes are dependent on both temperature and precipitation climatic factors [34], [59], [93], [168].…”
Section: Correlation and Time-lag Effects Between Modis Ndvi Data Ser...mentioning
confidence: 99%